Posyandu Cadre Assistance to Parents in Minimizing the Occurrence of Stunting in Parangargo Village, Wagir Subdistrict, Malang District - Wulandari, Arsyllah; Rasyad, Ach; Dayati, Umi (Proceedings Series of Educational Studies, 2024)
The purpose of study This For know How condition Stunting in Parangargo Village, you know factor background factors happen Stunting in Parangargo Village, you know assistance provided cadre posyandu in minimize happen Stunting as well as know obstacles experienced cadre posyandu in do assistance. Study This use approach qualitative study This carried out at Posyandu son people in Parangargo Village. Data is collected through technique interviews, observations, and studies documentation. Analysis of the data used in study This with stages data reduction, data presentation and drawing conclusions. Result of study This is (1). Condition Stunting in the village parangargo every year the more decrease. In 2022 cases Stunting experienced by 16 children, in 2023 it will decrease to 6 children and by 2024 it will reach 0 children. (2) Factors of occurrence filming in the village parangargo can be caused Because lack awareness public about Stunting, lack of source Power human (tbsp), lack of parental understanding and knowledge to health children and Stunting, behavior life healthy and clean or sanitation, lack of fulfillment food nutritious (3) Assistance provided cadre posyandu form assistance to cats, assistance to mothers pregnant, assistance Mother postpartum, assistance Clowns and Toddlers. And (4) Obstacles experienced cadre posyandu form limited amount cadre Posyandu, lack of coordination, communication cadre Posyandu and parents are lacking good, and funding is still minimal from Parangargo Village